The impact of pre-existing shoulder diseases and traumatic injuries of the shoulder on adhesive capsulitis in adult population: A population-based nested case-control study. Issue 39 (September 2019) - Tzeng, Chung-Yuh; Chiang, Hsiu-Yin; Huang, Chun-Che; Lin, Wei-Szu; Hsiao, Tzu-Hung; Lin, Ching-Heng
Abstract : Abstract: Adhesive capsulitis (AC) is a common chronic disorder for adult patients; however, whether a history of pre-existing shoulder diseases may affect the development of AC is still not fully understood. We aimed to investigate the incidence and prevalence of AC and to assess the association of pre-existing shoulder diseases and traumatic injuries of the shoulder with the development of AC in adults. This retrospective population-based cohort and nested case-control study used data from the National Health Institute Research Database of Taiwan. A total of 24, 414 patients aged 20 years or older and with a diagnosis of AC were identified between 2000 and 2013. We calculated the incidence of AC for each year during the study period. In addition, these AC patients were matched with controls (n = 97, 656) in a ratio of 1:4 based on age, gender, and index date. Univariate and multivariate logistic regression models were performed to identify variables associated with AC. Females and patients aged 50 to 69 years had higher age-gender standardized incidence and prevalence of AC than their counterparts. Multivariate analyses showed that after adjusting for relevant covariates, pre-existing shoulder diseases of calcific tendinitis (odds ratio [OR] = 8.74, 95% confidence interval [CI] = 5.66–13.5), biceps tendinitis (OR = 7.93, 95% CI = 5.33–11.79), rotator cuff syndrome (OR = 6, 95% CI = 5.26–6.85), osteoarthritis (OR = 4.27, 95% CI = 3.44–5.3), and impingement syndrome (OR = 3.13, 95% CI = 2.64–3.71), as well as fracture (OR = 4.51, 95% CI = 3.82–5.34) and dislocation (OR = 3.57, 95% CI = 2.35–5.45) of the shoulder were significantly associated with AC risk. Higher odds of AC were observed among patients with pre-existing shoulder conditions. This study highlights the need to consider differences in AC risk among patients with various types of shoulder diseases and traumatic injuries of the shoulder. Abstract : Supplemental Digital Content is available in the text